2015
DOI: 10.1007/8904_2015_437
|View full text |Cite
|
Sign up to set email alerts
|

Nitisinone Arrests but Does Not Reverse Ochronosis in Alkaptonuric Mice

Abstract: Alkaptonuria (AKU) is an ultrarare autosomal recessive disorder resulting from a deficiency of homogentisate 1,2 dioxygenase (HGD), an enzyme involved in the catabolism of phenylalanine and tyrosine. Loss of HGD function prevents metabolism of homogentisic acid (HGA), leading to increased levels of plasma HGA and urinary excretion. Excess HGA becomes deposited in collagenous tissues and subsequently undergoes polymerisation, principally in the cartilages of loaded joints, in a process known as ochronosis. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…Recently, a drug called nitisinone (2‐(2‐nitro‐4‐[trifluoromethyl]benzoyl)cyclohexane‐1,3‐dione; NTBC) that blocks 4‐hydroxyphenylpyruvic acid dioxygenase (HPPD; EC 1.13.11.27) which converts 4‐hydroxyphenylpyruvic acid (HPPA) into HGA was shown to prevent ochronosis in AKU mice, leading to a series of human clinical trials assessing nitisinone in AKU . The SONIA‐1 trial concluded that nitisinone effectively reduces HGA to a level likely to prevent ochronosis .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a drug called nitisinone (2‐(2‐nitro‐4‐[trifluoromethyl]benzoyl)cyclohexane‐1,3‐dione; NTBC) that blocks 4‐hydroxyphenylpyruvic acid dioxygenase (HPPD; EC 1.13.11.27) which converts 4‐hydroxyphenylpyruvic acid (HPPA) into HGA was shown to prevent ochronosis in AKU mice, leading to a series of human clinical trials assessing nitisinone in AKU . The SONIA‐1 trial concluded that nitisinone effectively reduces HGA to a level likely to prevent ochronosis .…”
Section: Introductionmentioning
confidence: 99%
“…1.13.11.27), the enzyme that produces HGA, and it is currently the most effective treatment for AKU. Nitisinone reduces plasma and urine HGA concentrations (Phornphutkul et al, 2002;Introne et al, 2011;Olsson et al, 2015;Ranganath et al, 2016;Milan et al, 2017), completely arrests ochronosis in AKU mice (Preston et al, 2014;Keenan et al, 2015) and more recently was shown to slow progression of morbidity in patients attending the UK NAC (2mg nitisinone daily) (Ranganath et al, 2018). We showed previously in serum and urine that nitisinone induced an extended network of metabolic alteration within tyrosine and neighbouring pathways, including tryptophan, purine and TCA cycle (Davison et al, 2019a;Norman et al, 2019).…”
Section: Associated Alteration To Tyrosine Purine and Tca Cycle Metamentioning
confidence: 94%
“…In AKU mice administration of p‐hydroxyphenylpyruvate dioxygenase (EC:1.13.11.27; HPPD) inhibitors, such as nitisinone, soon after birth resulted in failure to pigment, while a similar administration of HPPD inhibitors during the middle of the life span of the mouse, when pigmentation has already developed, prevented progression, but not reversal, of pigmentation . This suggests that HPPD inhibitors, by decreasing HGA, can modify the OP process in AKU mice.…”
Section: Formation Of Ochronotic Pigmentmentioning
confidence: 99%